2000
DOI: 10.1067/mva.2000.104569
|View full text |Cite
|
Sign up to set email alerts
|

The durability of endovascular treatment of multisegment iliac occlusive disease

Abstract: Endovascular therapy for multisegment aortoiliac occlusive disease has acceptable patency rates; however, reintervention is often needed. The presence of external iliac artery disease is a significant predictor of poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…However, several factors such as presence of external iliac occlusive disease, vessel calcification, and totally occluded iliac arteries have been associated with high complication rate and poor long-term durability when treated with bare metal stents. 20,21 Use of stent grafts in iliac occlusive disease has increased in popularity in recent years. 19,22 We have previously reported 12-month primary patency of 70% in patients treated with stent grafts for iliac occlusive disease (with and without femoral endarterectomy), which appeared to have superior patency compared with historical controls treated with bare metal stents.…”
Section: Discussionmentioning
confidence: 99%
“…However, several factors such as presence of external iliac occlusive disease, vessel calcification, and totally occluded iliac arteries have been associated with high complication rate and poor long-term durability when treated with bare metal stents. 20,21 Use of stent grafts in iliac occlusive disease has increased in popularity in recent years. 19,22 We have previously reported 12-month primary patency of 70% in patients treated with stent grafts for iliac occlusive disease (with and without femoral endarterectomy), which appeared to have superior patency compared with historical controls treated with bare metal stents.…”
Section: Discussionmentioning
confidence: 99%
“…BOSCH et al, showed that the clinical presentation (claudication versus critical ischaemia) is an important determinant of long-term success (12). POWELL et al, in a retrospective study that included 87 patients who underwent 207 iliac artery PTAs and 115 iliac artery stenting procedures, identified only the presence of an EIA lesion as a predictor of decreased long-term patency (19). In a larger study that included 67 women and 122 men who underwent 247 percutaneous procedures, TIMARAN C. H. et al identified EIA stenting as an independent predictor of decreased patency in women but not in men (20).…”
Section: Resultsmentioning
confidence: 98%
“…Although operative management is recommended for advanced AIOD lesions, these lesions encompass many different patterns of disease, some of which are amenable to rather straightforward endovascular interventions. Endovascular treatment of EIA lesions has also been questioned, [10][11][12][13] and by implication, treatment of a combination of ipsilateral EIA and CIA lesions may be associated with poorer results than treatment of isolated CIA or EIA lesions. However, few reports have focused on results of endovascular treatment of ipsilateral CIA and EIA lesions.…”
Section: Discussionmentioning
confidence: 97%
“…The data here, therefore, may suggest the length of diseased artery treated endovascularly in the iliac artery position is less important than generally believed if stents are routinely used in the iliac arteries, as prior studies indicating increased length of diseased segment treated portended poorer outcomes were based on selective rather than routine stenting. 13,18 Failure of a prosthetic infrainguinal graft or an infrainguinal catheter-based procedure may lead to deterioration of the patient's prospects of subsequent operative intervention. 19,20 Our data with respect to AIOD, however, indicate late open conversion for failed PTAS of AIOD is infrequently required, and there seem to be no differences in the rate or types of subsequent open operative procedures required for failure of endovascular treatment of AIOD, regardless if the patient was initially treated for an isolated iliac lesion or a combination of ipsilateral CIA and EIA lesions.…”
Section: Discussionmentioning
confidence: 99%